ANALISIS PERUBAHAN KADAR LOGAM TEMBAGA (Cu) PADA PENAMBAHAN ION PERAK (Ag) DENGAN METODE ELEKTROKOAGULASI - Agustin Pratiwi; Bohari Yusuf; Rahmat Gunawan (JURNAL KIMIA MULAWARMAN, 2015)
The analysis of changes in levels of copper (Cu) on the addition of silver ions (Ag) with electrocoagulation method has been researched by using Atomic Absorption Spectrophotometer (AAS) as an instrument for the determination of levels. The addition of ionic silver (Ag) in a solution of copper (Cu) using varying concentrations of silver (Ag) 4, 6, 8, 10 and 12 ppm. The results showed that the effect of the addition of ionic silver (Ag) 4,6, 8, 10 and 12 resulted in changes in the levels of copper (Cu) are deposited successively in the ppm concentration is 9.375; 9.324; 9.272; 9.168; 9.142 and 9.116. Metalcontentof silver(Ag) in a medium containing copper (Cu) with a variety of metallic silver( Ag) differentat 4, 6, 8, 10 and 12ppm after the electrocoagulation metal contentof silver(Ag) depositedin the amount3.99; 5.99; 7.96; 9.91 and 11.88ppm.